X-ray variability in LINERs. Issue Volume 9:Issue S304(2013) (25th July 2014) - Masegosa, Josefa; Hernández-García, Lorena; Márquez, Isabel; González-Martín, Omaira
Abstract: One of the most important features in active galactic nuclei (AGN) is the variability of their emission. Variability has been discovered at X-ray, UV, and radio frequencies on time scales from hours to years. Among the AGN family and according to theoretical studies, Low-Ionization Nuclear Emission Line Region (LINER) nuclei would be variable objects on long time scales. Our purpose is to investigate spectral X-ray variability in LINERs and to understand the nature of these kinds of objects, as well as their accretion mechanism. Chandra and XMM –Newton public archives were used to compile X-ray spectra of LINER nuclei at different epochs with time scales of years. To search for variability we fit all the spectra from the same object with a set of models, in order to identify the parameters responsible for the variability pattern. We found that long term spectral variability is very common, with variations mostly related to hard energies (2-10 keV). These variations are due to changes in the soft excess, and/or changes in the absorber, and/or intrinsic variations of the source.